Lightweight, latency‐aware routing for data compression in wireless sensor networks with heterogeneous traffics. Issue 9 (16th March 2015) - Wang, You‐Chiun; Wei, Chia‐Ting
Abstract: In many applications and scenarios, sensors have to regularly report what they monitor from the environment and quickly notify the sink node of event occurrence in the sensing field. An in‐network data reduction technique, such as data aggregation and data compression, can help diminish the amount of data sent from sensors, which not only saves the network bandwidth but also preserves sensors' energy. However, such technique does not consider packet latency because of the aggregation or compression operation. When some sensors generate regular reports in lower data rates, their packets have to spend longer time to be aggregated or compressed, resulting in higher packet delays. Besides, when events occur, the network could suffer from instant congestion due to the generation of numerous event notifications. Motivated with the aforementioned observations, the paper develops a lightweight, latency‐aware routing for data compression (L2DC) scheme to reduce packet latency when applying the compression technique, to reduce the amount of data generated from sensors. L2DC gives event notifications a higher priority over regular reports and eliminates unnecessary notifications to avoid bursty network congestion. In addition, L2DC facilitates the data compression process by allowing each sensor to determine whether to keep packets for compression locally or to send them to a neighbor to be compressed in a distributed manner. Our L2DC scheme can be easily built on most ad hoc and sensor routing protocols because it provides auxiliary redundant packet elimination and relay node selection mechanisms to reduce packet latency. By using the ad hoc on‐demand distance vector protocol as the example, simulation results demonstrate the effectiveness of the L2DC scheme. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We point out that data compression will significantly increase packet latency in a wireless sensor network. To solve this problem, an efficient L2DC scheme is developed to help each sensor adaptively select the neighbor to compress packets and discard unnecessary event notification. Simulation results verify that L2DC can reduce packet latency while saving sensors' energy.